Development of New Biosorbent Based on Crosslinked Chitosan Beads with High Brilliant Blue FCF Removal Efficiency - Fatiha Lahgui; Beatriz Delgado Cano; Antonio Avalos Ramirez; Michèle Heitz; Hafida Hadjar; Samia Kaddour (Molecules)
Effluents containing synthetic anionic dyes can pose a risk to ecosystems, and they must be treated before their release to the environment. Biosorption, a simple and effective process, may be a promising solution for treating these effluents. In this work, chitosan beads were crosslinked with epichlorohydrin to produce a highly stable and performant biosorbent to remove Brilliant Blue FCF dye. The biosorbent was characterized by determining the functional groups on its surface, as well as its elemental composition, crystallinity, and surface morphology. Crosslinking with epichlorohydrin significantly improved the biosorption capacity of chitosan beads. A maximum biosorption capacity of 600 mg/g corresponding to 99% removal efficiency was observed at pH 3.0, a biosorbent dose of 0.5 g/L, an initial dye concentration of 300 mg/L, a contact time of 10 h, and a temperature of 323 K. The biosorption of Brilliant Blue FCF dye in chitosan beads crosslinked with epichlorohydrin was well described by the Langmuir isotherm and followed an adsorption kinetic of pseudo second order. The thermodynamic parameters indicate a spontaneous biosorption process. The presence of anions such as NO3− and SO42− could interfere with the biosorption of Brilliant Blue FCF on the chitosan crosslinked beads, but Cl− did not interfere in biosorption process. Over three biosorption/desorption cycles, the biosorbent showed a removal efficiency of 97% and a desorption rate of over 98%. Chitosan is available worldwide and is a low-cost biomaterial, presenting high potential to be used as a biosorbent to treat industrial effluents containing anionic compounds, such as dyes.